2010
DOI: 10.1128/aem.00245-10
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Enteric Viruses in Source Waters for Drinking Water Production in the Netherlands

Abstract: The quality of drinking water in the Netherlands has to comply with the Dutch Drinking Water Directive: less than one infection in 10,000 persons per year may occur due to consumption of unboiled drinking water. Since virus concentrations in drinking waters may be below the detection limit but entail a public health risk, the infection risk from drinking water consumption requires the assessment of the virus concentrations in source waters and of the removal efficiency of treatment processes. In this study, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 46 publications
6
59
0
4
Order By: Relevance
“…In contrast, other studies have shown some correlation between human viruses and F-specific phages [23,123,126,140,141] and between human viruses and somatic coliphages in surface waters [104,140,142], between enteroviruses and somatic coliphages in sludge [82], and between human viruses and both somatic and F-specific phages in surface water [78]. Thus, even if the results far from indicate a clear correlation between indicator coliphage densities and human viruses in water, there is evidence that somatic and F-specific coliphages are more strongly associated with pathogenic viruses than the traditional bacterial indicators and even a particular pathogenic virus.…”
Section: Relationship To Human Virusesmentioning
confidence: 56%
See 2 more Smart Citations
“…In contrast, other studies have shown some correlation between human viruses and F-specific phages [23,123,126,140,141] and between human viruses and somatic coliphages in surface waters [104,140,142], between enteroviruses and somatic coliphages in sludge [82], and between human viruses and both somatic and F-specific phages in surface water [78]. Thus, even if the results far from indicate a clear correlation between indicator coliphage densities and human viruses in water, there is evidence that somatic and F-specific coliphages are more strongly associated with pathogenic viruses than the traditional bacterial indicators and even a particular pathogenic virus.…”
Section: Relationship To Human Virusesmentioning
confidence: 56%
“…The ratios of culturable viruses to somatic coliphages (mainly with reference to enteroviruses detected by cell culture) are 10:10 4 or 10:10 5 in the scenarios for which data on both are available. The claim is true for raw sewage, secondary and tertiary effluents [72][73][74][75][76][77], surface waters [73,[78][79][80], and sludge [81,82]. The same ratio is true for infectious rotaviruses detected by cell culture followed by qRT-PCR [83].…”
Section: Concentration Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Evaluation of surface water quality in drinking water sources is important as they can be one of the main pathways for the dissemination of toxic chemicals and pathogenic microorganisms [2,3]. Identifying the source(s) of contamination and developing appropriate management strategies is essential to minimizing potential public health risks [4].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of enteroviruses in coastal waters in both bathing and non-bathing sites is documented worldwide [45][46][47][48][49][50]. Enteroviruses have also been found in rivers [49,[51][52][53][54][55], lakes [56,57], groundwater [29, [58][59][60][61] and in both untreated and finished drinking water supplies [30,38,55,62,63]. Despite the widespread presence of these viruses, however, few drinking water-related outbreaks have been reported [64][65][66][67], only two outbreaks of recreational waterborne coxsackievirus, nine echovirus outbreaks concentrated between 1990 and 2005 [11] and sporadic echovirus 30 outbreaks in swimming pool.…”
Section: Enterovirusmentioning
confidence: 99%